2021
DOI: 10.21425/f5fbg51267
|View full text |Cite
|
Sign up to set email alerts
|

The two South American dry diagonals

Abstract: South American drylands roughly form two diagonals both termed in the biogeographical literature as the "South American dry diagonal" (SADD). However, they correspond to two different geographical areas. One comprises the Caatinga, Cerrado and Chaco domains, thus encompassing the areas between northeastern Brazil and northwestern Argentina. The other stretches from Patagonia in southern Argentina to the Pacific deserts of northern Chile and Peru, thus also including the Monte, Prepuna and dry Puna domains. I t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 94 publications
0
21
0
2
Order By: Relevance
“…The DEC+J model suggests a northward dispersal along the Andean foothills. Both scenarios require a shift from winter into a summer rain ecology of the ancestor of Cristaria multifida , two major climatic regimes that, during arid phases, are separated by a pronounced climatic barrier called the Western South American Dry Diagonal (WSADD; Luebert, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The DEC+J model suggests a northward dispersal along the Andean foothills. Both scenarios require a shift from winter into a summer rain ecology of the ancestor of Cristaria multifida , two major climatic regimes that, during arid phases, are separated by a pronounced climatic barrier called the Western South American Dry Diagonal (WSADD; Luebert, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, the DOF was thought to harbour continuous low‐diversity open vegetation with no regional differentiation (Vanzolini, 1963). However, recent research has demonstrated that the region is rich in species diversity and endemism and acts as an effective barrier for biotic exchange between Amazonia and Atlantic rainforests (Antonelli et al, 2018; Ledo & Colli, 2017; Luebert, 2021; Werneck, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The biogeographic cluster 1 corresponds with a broad ‘pan-Amazonian’ region that relied on the ancient Amazon Craton ( Hoorn et al, 2010 ). Cluster 2 broadly groups different formations of the area known as the ‘Dry Diagonal’ ( Prado and Gibbs, 1993 ; Luebert, 2021 ), which are geologically younger, dating from the Miocene ( Pennington et al, 2006 ; Beerling and Osborne, 2006 ; Becerra, 2005 ). Although lineage crown ages do not differ between these regions ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%